2011
DOI: 10.1080/15459624.2011.585927
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Three Biological Decontamination Methods on Filtering Facepiece Respirator Fit, Odor, Comfort, and Donning Ease

Abstract: The objective of this study was to determine if ultraviolet germicidal irradiation (UVGI), moist heat incubation (MHI), or microwave-generated steam (MGS) decontamination affects the fitting characteristics, odor, comfort, or donning ease of six N95 filtering facepiece respirator (FFR) models. For each model, 10 experienced test subjects qualified for the study by passing a standard OSHA quantitative fit test. Once qualified, each subject performed a series of fit tests to assess respirator fit and completed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
258
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(268 citation statements)
references
References 18 publications
(24 reference statements)
8
258
0
2
Order By: Relevance
“…Heimbuch et al 4 and Lore et al 5 demonstrated 3 energetic decontamination methods—microwave-generated steam, low-temperature moist heat, and ultraviolet germicidal irradiation—that inactivate H1N1 and H5N1 influenza viruses without significantly affecting FFR fit or function. 6,7 Other chemical and energetic methods have also shown promise for decontamination of FFRs, 810 but we found no studies that addressed decontamination of bacterial agents on FFRs.…”
mentioning
confidence: 89%
“…Heimbuch et al 4 and Lore et al 5 demonstrated 3 energetic decontamination methods—microwave-generated steam, low-temperature moist heat, and ultraviolet germicidal irradiation—that inactivate H1N1 and H5N1 influenza viruses without significantly affecting FFR fit or function. 6,7 Other chemical and energetic methods have also shown promise for decontamination of FFRs, 810 but we found no studies that addressed decontamination of bacterial agents on FFRs.…”
mentioning
confidence: 89%
“…Viscusi et al 36 collected participants’ responses to several subjective criteria in a study of effects of decontamination on 6 FFR models. The following FFRs were used in the study: 3M 8000, 3M 8210, Moldex 2200N95 (Moldex-Metric, Culver City, CA), 3M 1860, 3M 1870, and Kimberly-Clark PFR95-270 (Kimberly-Clark, Roswell, GA).…”
Section: Resultsmentioning
confidence: 99%
“…This study did not consider lateral bending because the respirator fit test does not require lateral bending movement (OSHA, 1999; Viscusi et al ., 2011). The total head movements were the summation of seven relative movements of C0–C1 to C6–C7.…”
Section: New Headform Modelsmentioning
confidence: 99%